2016
DOI: 10.7860/jcdr/2016/18084.7980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preheated Composite on Micro leakage-An in-vitro Study

Abstract: IntrOductIOnDirect composite restorations are gaining an increased popularity over the conventional amalgam restorations due to esthetic demands and concerns regarding mercury in amalgam [1]. The clinical success of the composite restorations is very much dependent on its polymerization and degree of conversion. Highly viscous composites are very hard to adapt accurately to cavity preparations and may leave behind unwanted voids, hence, more flowable composites with less filler content were introduced. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
0
22
0
7
Order By: Relevance
“…Meanwhile, DC is influenced by several factors, such as light exposure conditions, composition, shade, opacity, and thickness of the RBC, pre-cure temperature also plays an important role in the polymerization process [ 5 , 6 ]. As the success of RBC restorations depends on their polymerization and DC, the influence of temperature has become one of the central issues of several studies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, DC is influenced by several factors, such as light exposure conditions, composition, shade, opacity, and thickness of the RBC, pre-cure temperature also plays an important role in the polymerization process [ 5 , 6 ]. As the success of RBC restorations depends on their polymerization and DC, the influence of temperature has become one of the central issues of several studies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by several investigations, pre-heating may have a beneficial impact on marginal adaptation, gap formation, and microleakage by reducing the viscosity of RBCs [ 7 , 14 , 15 ]. Improved handling properties, such as flowability can facilitate the application of the filling material, consequently making the procedure less time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have found that rise in pulpal temperature only by 0.8 • C after placement of a 60 • C preheated composite resin while an increase of 5 • C pulpal temperature is seen after 20s of light curing. 12 Daronch et al found that after removing composites from heating device, 50% of the temperature attained will be lost after 2 minutes and almost 90% will be lost after 5 minutes. • Light of dental unit chair can also be used clinically in order to warm composites.…”
Section: Preheating Compositesmentioning
confidence: 99%
“…Nevertheless, studies have found that pulp temperature is raised only by 0.8°C after placement of a 60°C preheated composite resin while 20s of light curing increases pulp temperature by 5°C. 10 The term "Degree of Conversion" (DC%), can be defined as the monomeric carbon-carbon double bonds conversion into polymeric carbon-carbon single bonds, the importance of increasing the conversion and thus increased crosslinkage results in improvement in properties as higher surface hardness, flexural strength, fracture toughness, and tensile strength. 11 Low degree of conversion can affect mechanical properties of the cement and results in increase in solubility, water sorption and subsequently affect its color stability 12 .…”
Section: Introductionmentioning
confidence: 99%